(untitled) (Eurasian Journal of Engineering and Technology, 2023)
This article compares the Uster Statistics 2018 with the 50% indicators of the yarns obtained by changing the flow of fibres coming out of the output cylinders of the spun yarns from the ring spinning machine at different angles.